Information System Success Factors and Their Influence on Employee Performance in a Digital Environment - Senin, Nurul Syahirah; Rashid, Umi Kartini (JBS Nexus, 2025)
The banking sector is rapidly evolving with advancements in information systems and AI. This study examines key factors influencing their adoption among employees, assessing their impact on job performance and challenges to implementation. Using the DeLone and McLean Information Systems Success Model, data from banking employees will be analyzed through PLS-SEM. Findings will provide insights into adoption determinants, performance benefits, and barriers, contributing to the digital transformation of banking. The study highlights the need for strategic integration of AI and information systems to enhance workforce efficiency.